Implementation of Slum Management Policies in Realizing Sustainable Development - Nuryadi, Ida; Daraba, Dahyar; Lukman, Sampara; Santoso, Eko Budi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The research is based on an imbalance between the carrying capacity of cities and population growth which has led to the development of slums in urban areas. Likewise, the development of the industrial sector has become a magnet for urbanization and population growth, while the community's ability to obtain decent housing is still low. The research intends to examine how the implementation of slum settlement policies is implemented and to design a model for handling slum settlements. Grindle's (1980) policy implementation model consists of the dimensions of the policy content context with aspects of 1) the interests affected; 2) type of benefit; 3) the degree of change; 4) the decision-making position; 5) program implementers; 6) policy resources, as well as the implementation context with aspects of 1) the strengths and strategies of the actors involved; 3) the characteristics of the ruling institutions and regimes; 3) compliance and responsiveness of the target group. This research uses a qualitative descriptive method with primary data obtained through interviews and observations. While data analysis techniques used descriptive analysis techniques including data condensation, data presentation and drawing conclusions (Miles and Huberman, 2014). The research finding is that the policy for dealing with slum settlements through the Berseka Program has not been optimally implemented in terms of the insignificant contribution to handling slum settlements. So a more comprehensive and sustainable approach is needed in dealing with slum settlements. The results of the study concluded: 1) The Berseka program has not been optimally implemented in terms of the low perceived benefits, low degree of change, weak government control over the actors involved, and lack of program sustainability and post-handling maintenance; 2) A comprehensive sustainable comprehension slum handling model developed by researchers includes approaches to prevention, revitalization, relocation, and preservation that will increase achievements in building cities and settlements that are inclusive, safe, resilient and sustainable. Research suggestions: 1) Need to study the role of the private sector and NGOs in dealing with slum settlements; 2) The need for complementary policies in the context of preventing slum settlements in the form of Regional Regulations and District Head Regulations.